2020
DOI: 10.1186/s12885-020-07680-w
|View full text |Cite
|
Sign up to set email alerts
|

A novel circular RNA hsa_circRNA_103809/miR-377-3p/GOT1 pathway regulates cisplatin-resistance in non-small cell lung cancer (NSCLC)

Abstract: Background Cisplatin is the first-line chemotherapeutic drug for non-small cell lung cancer (NSCLC), and emerging evidences suggests that targeting circular RNAs (circRNAs) is an effective strategy to increase cisplatin-sensitivity in NSCLC, but the detailed mechanisms are still not fully delineated. Methods Cell proliferation, viability and apoptosis were examined by using the cell counting kit-8 (CCK-8) assay, trypan blue staining assay and Annex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Cisplatin-resistance is a huge obstacle to make this drug ineffective to treat NSCLC in clinic [13][14][15], and uncovering the potential underlying mechanisms will help to solve this problem. According to recent publications [16,44,46,47], miRNAs with post-transcriptional activities are crucial for regulating cancer progression and drug resistance, and multiple miRNAs that regulate cisplatin-resistance in NSCLC have been screened out, such as let-7 miRNA [16], miR-497-5p [46], miR-130a [47] and miR-377-3p [44]. Among all the miRNAs, miR-556-5p has also been reported to be closely associated with cancer progression, and its role in regulating cancer development varies according to differential cancer types [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cisplatin-resistance is a huge obstacle to make this drug ineffective to treat NSCLC in clinic [13][14][15], and uncovering the potential underlying mechanisms will help to solve this problem. According to recent publications [16,44,46,47], miRNAs with post-transcriptional activities are crucial for regulating cancer progression and drug resistance, and multiple miRNAs that regulate cisplatin-resistance in NSCLC have been screened out, such as let-7 miRNA [16], miR-497-5p [46], miR-130a [47] and miR-377-3p [44]. Among all the miRNAs, miR-556-5p has also been reported to be closely associated with cancer progression, and its role in regulating cancer development varies according to differential cancer types [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…The parental cisplatin-sensitive NSCLC (CS-NSCLC) cells (A549 and H1299) were purchased from The Chinese Academy of Sciences Cell Bank (Shanghai, China), and the cells were cultured in the DMEM medium (Gibco, CA, USA) supplemented with 10% fetal bovine serum (FBS, Gibco, CA, USA), 1% penicillin and streptomycin (Sigma-Aldrich, St. Louis, MO, USA). The cells were placed in an incubator with 5% CO 2 humidified air at 37°C, and the CS-NSCLC cells were subjected to long-term low-dose cisplatin exposure (0.5–5 μg/ml, 80 days) to establish cisplatin-resistant NSCLC (CR-NSCLC) cells (A549/DDP, H1299/DDP) following the experimental procedures provided by the previous work [ 44 ], and the CR-NSCLC cells were maintained in the complete medium containing 1 μg/ml cisplatin, which were subsequently subjected to high-dose cisplatin (25 μg/ml) treatment and 1 mM of pyroptosis inhibitor Necrosulfonamide (NSA, HY-100573, MedChem Express) for 0 h, 6 h, 12 h, 18 h, 24 h and 48 h.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence has demonstrated that circRNAs are implicated in CDDP resistance in lung cancer. Knockdown or silencing of certain circRNAs suppresses CDDP resistance in NSCLC such as circ-RNF121, circ_0076305, circRNA_103615, circ_0008928, hsa_circRNA_103809, circ-PRMT5, and circ_0007385 (17,18,49,(62)(63)(64)(65). Additionally, circAKT3 inhibits glycolysis balance and enhances CDDP resistance, whereas circRNA-FOXO3 accelerates glycolysis and promotes CDDP sensitivity (50,51).…”
Section: Circrnas and Lung Cancer Drug Resistancementioning
confidence: 99%
“… 70 Typically, a few inorganic-based therapeutic agents are briefly reviewed from a chemical point of view. Platinum-based therapeutic agents, such as cisplatin, 72 carboplatin 73–75 and oxaliplatin, 76–78 and a ruthenium( iii ) complex 79 have been well explored in the drug-delivery field.…”
Section: Inorganic–inorganic Nanohybrids For Drug Deliverymentioning
confidence: 99%